Hatcheries’ contamination: the molecular characterization and pathogenicity of Mycoplasma gallisepticum isolates in China - Huanxin Fang; Chunyan Zhang; Qi Li; Pei Li; Sixiang Xu; Libin Tan; Xihui Zhu; Xiangkuan Zheng; Rui Tian; Zitai Qi; Chenxi Li; Yanfei Yu; et al. (Poultry Science, 2025)
Mycoplasma gallisepticum (M. gallisepticum) is a significant pathogenic microorganism contaminating poultry hatchery environments. During intensive hatching, M. gallisepticum significantly impairs embryonic health and development, ultimately reducing embryonic vitality. Clinically, it is common for affected embryos to exhibit incomplete pipping of eggshell, a condition referred to as pipping failure embryos (PFEs). Critically, live PFEs exhibit high M. gallisepticum shedding, substantially increasing the risk of M. gallisepticum transmission to healthy chicks at early-stage within the same space. These asymptomatic infected chicks often develop chronic respiratory disease (CRD) under stress during subsequent growth. This study investigated M. gallisepticum contamination in hatchery environments and isolated M. gallisepticum strains from live PFEs. A total of 1,200 environmental samples collected from 16 hatcheries across eight provinces in China showed M. gallisepticum positivity rates exceeding 80 % in both dust and feather samples. Among 888 live PFEs, the M. gallisepticum positivity rate was 79.62 %, with a 100 % positivity rate observed in Sichuan Province. Molecular typing of 29 M. gallisepticum isolates using partial mgc2 revealed four distinct clusters: China I Clade, China II Clade, R Clade, and 685 Clade. Notably, China I Clade strains formed a unique cluster distinct from isolates obtained from 12 other countries. Subsequently, one isolate from each of 4 clusters was selected for pathogenicity tests. The result suggested the China I Clade GDya_38 isolate demonstrated significantly higher virulence in 8-day-old specific-pathogen-free (SPF) chicken embryos yolk sac inoculation experiments, inducing severe incomplete pipping. Additionally, tracheal challenge in 15-day-old SPF chicks revealed that GDya_38 caused more severe airsacculitis compared to other isolates.In conclusion, severe M. gallisepticum contamination has been identified in hatchery environments across China, with the unique China I Clade GDya_38 isolate exhibiting heightened pathogenic potential. This strain's capacity for vertical transmission, leading to embryonic vitality impairment, and horizontal transmission, causing CRD symptoms, underscores its substantial threat to poultry production.